Characterization of aroma changes in human milk during storage at -19°C - Spitzer, Johanna; Büttner, Andrea (Food Chemistry, 2010)
Breastfeeding is believed to impart major beneficial effects on babies, due to various human-specific components. Compatibility of family and profession, however, often necessitates the pumping of breast milk and its storage under diverse conditions, either in a refrigerator, freezer or for brief periods at room temperature. The present study investigates the formation of a characteristic fish-like and metallic off-odour during the conventional storage of human milk that does not develop during cow milk storage, and elucidates the molecular factors for these specific aroma changes. Odorants in fresh and stored human milk containing the specific fishy-metallic off-odour were characterized by means of gas chromatography-olfactometry and identified based on their mass spectrometric data and specific chromatographic and sensory characteristics. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dchph.llmch.charac
Keywords: (Z)-1; 5-octadien-3-one; Breastfeeding; Fishy; Gas chromatography-olfactometry; Off-flavour